Anglicanism, Missions and Empire : The Eighteenth and Nineteenth Centuries - Strong, Rowan, (Anglican-Episcopal Theology and History ;, 2025)
In Anglicanism, Empire and Missions Rowan Strong offers fresh insights into Christian missions, illuminating both large-scale movements and smaller, local initiatives. Tracing the origins of Anglican missions back to the foundation of the Society for the Propagation of the Gospel in Foreign Parts in 1701, the work explores their evolution-from a transatlantic context in the eighteenth century to a truly global presence within the expanding British Empire of the nineteenth century. Contemporary Anglophone mission historiography has often overlooked Anglican missionary endeavours during this period, instead privileging the activism of Evangelical missions. This volume redresses the balance, revealing the far-reaching influence of Anglican mission leaders and societies and restoring their rightful place in the broader history of Christian missions.